Awareness of invasion of privacy on social networking site among youth in Malaysia: a case study of facebook - Low, Soo Yong (2011)
Youths’ participations in social networking sites have dramatically increased recently. Facebook allows users to create profile and share their identity information with wide network of friends, regardless those ‘friends’ are their actual friends or strangers. Numerous studies have shown that users low concerned with the bad consequences of information they posted online. Hence, this study intends to examine the awareness on invasion of privacy on Facebook among youth. Besides, this study will discuss about patterns of Facebook’s adoption as well as Facebook’s trustworthiness. Survey approach had been employed to find out the level of awareness on invasion of privacy. Hundred of UTAR students were chosen as respondent by using purposive sampling method. This method is chosen due to the respondents have to be a Facebook user and from the age group of 18 to 24. Hundred sets of questionnaire, which consisted of 26 questions, had been distributed. From the finding, it shows that the awareness of invasion of privacy is considered at moderate level. While, women have greater concern on their privacy compared to men. Thus, Facebook should put more efforts on strengthening its privacy system in order to provide a safer social networking site to users.